2006
DOI: 10.1289/ehp.8561
|View full text |Cite
|
Sign up to set email alerts
|

National Prevalence and Exposure Risk for Cockroach Allergen in U.S. Households

Abstract: We characterized the prevalence of cockroach allergen exposure in a nationally representative sample of U.S. homes and assessed risk factors for elevated concentrations.DesignWe used data from the National Survey of Lead and Allergens in Housing, a population-based cross-sectional survey.ParticipantsParticipants were residents of 831 U.S. homes in the survey.Evaluations/MeasurementsWe analyzed allergen, questionnaire, and observational data of 831 U.S. homes.ResultsCockroach allergen (Bla g 1) concentrations e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 23 publications
(34 reference statements)
2
77
0
1
Order By: Relevance
“…9,54 Our levels are likely less comparable to national data, because these data are generally less representative of the urban context; for example, they contain few high-rise buildings. 10,51,77,85 From this examination, we begin to understand how building-level characteristics may be related to allergen levels. We did not find associations between building-level characteristics and Der f 1 or Fel d 1 allergen in bivariate or fully adjusted linear models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,54 Our levels are likely less comparable to national data, because these data are generally less representative of the urban context; for example, they contain few high-rise buildings. 10,51,77,85 From this examination, we begin to understand how building-level characteristics may be related to allergen levels. We did not find associations between building-level characteristics and Der f 1 or Fel d 1 allergen in bivariate or fully adjusted linear models.…”
Section: Discussionmentioning
confidence: 99%
“…3,16,21,22,[24][25][26][42][43][44][45][46][47] An emerging literature does suggest that indoor allergens associated with asthma are related to the buildings in which people live. 10,11,[48][49][50][51][52] Considerable literature firmly establishes that the presence of cockroaches and rodents (i.e., pests) is associated with higher levels of asthma morbidity. 5,10,24,51,[53][54][55][56][57] Likewise, recent literature has highlighted the relationship between asthma morbidity and building types such as public housing; 54,58 mixed-use buildings, i.e., property containing both residential and commercial space; [59][60][61] and building size.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the National Survey of Lead and Allergens in Housing have shown that people in the above high school education category have a higher mean level of cat allergen in their homes than people in the lower education categories whereas people living in highly populated metropolitan areas are more likely to have elevated levels of cockroach allergen in their homes than people living in other areas. 16,17 In addition, studies from rural areas in Europe have consistently shown that children growing up on farms are less likely to develop atopy and allergic disease, 18 the presumption being that certain microbial exposures in early childhood may be beneficial. However, in NHANES III, the urbanization category "all other areas" consists only partially of rural or farm families, so it is not known whether any differences in the PAR by urbanization can be attributed to a protective effect of rural or farm exposures.…”
Section: Discussionmentioning
confidence: 99%